Physical Fitness and Learning Achievment Pesantren and Non Pesantren Students at SMK Takhasus Plus Al Mardiyah Kendal in 2020 - WALIDAINI, FARID; Rahayu, Setya; Hidayah, Taufik (Journal of Physical Education and Sports, 2021)
Two groups of pesantren and non-pesantren students at SMK Takhasus Plus Al Mardiyah Kendal raised concerns about differences in physical fitness and learning achievement between these groups. So it is required an identification on physical fitness and student achievement at two groups students and it is also required to identify interaction between physical fitness and learning achievement students. The research method used quantitative. The subjects in this study were 85 students of SMK Takhasus Plus Al Mardiyah Kendal, and it used purposive sampling technique. The research instrument was physical fitness test data and learning achievement. The data analysis technique used different tests. The results of the analysis show that there were differences in the physical fitness of the two groups of students, but there was no difference in the level of student achievement, and it was known that the level of physical fitness was able to affect the learning achievement of pesantren and non- pesantren students. The advice given is that students should pay more attention to their physical fitness by doing various physical activities that can support teaching and learning activities, it should be able to provide more portions for pesantren students in terms of physical exercise to improve children's physical fitness.